The meaning of a very positive birth experience: focus groups discussions with women. Issue 1 (December 2015) - Karlström, Annika; Nystedt, Astrid; Hildingsson, Ingegerd
Abstract Background The experience of giving birth has long-term implications for a woman's health and wellbeing. The birth experience and satisfaction with birth have been associated with several factors and emotional dimensions of care and been shown to influence women's overall assessment. Individualized emotional support has been shown to empower women and increase the possibility of a positive birth experience. How women assess their experience and the factors that contribute to a positive birth experience are of importance for midwives and other caregivers. The aim of this study was to describe women's experience of a very positive birth experience. Method The study followed a qualitative descriptive design. Twenty-six women participated in focus group discussions 6–7 years after a birth they had assessed as very positive. At the time of the birth, they had all taken part in a large prospective longitudinal cohort study performed in northern Sweden. In the present study, thematic analysis was used to review the transcribed data. Results All women looked back very positively on their birth experience. Two themes and six sub-themes were identified that described the meaning of a very positive birth experience. Women related their experience to internal (e.g., their own ability and strength) and external (e.g., a trustful and respectful relationship with the midwife) factors. A woman's sense of trust and support from the father of the child was also important. The feeling of safety promoted by a supportive environment was essential for gaining control during birth and for focusing on techniques that enabled the women to manage labour. Conclusion It is an essential part of midwifery care to build relationships with women where mutual trust in one another's competence is paramount. The midwife is the active guide through pregnancy and birth and should express a strong belief in a woman's ability to give birth. Midwives are required to inform, encourage and to provide the tools to enable birth, making it important for midwives to invite the partner to be part of a team, in which everyone works together for the benefit of the woman and child.